The balance before and after dehydration: an experiment to see the difference - Purnomo, Muhammad Iqbal; Roldan, Patrick John B.; Cabarles, John Paul A.; Quinto, Janna Marie B.; Garcia-Jimenez, Jose Vicente (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. Balance is the ability to maintain the position of the body when standing, doing activities, also useful equilibrium, posture in order to be able to perform movement activities properly, water is very important for humans which is useful for maintaining cell hemostasis, fluid management interventions that pay attention to intek and output records that te Physical activity is a movement that involves muscles and energy working harder. This study aims to determine the difference in the effect before and after dehydration on body balance.Material and Methods. This research is a descriptive experiment. This research was conducted at the Sultan Syarif Abdurahman stadium field, Pontoianak City. The population used Sports Coaching Education students. Purposive sampling technique so that 16 students were sampled. The treatment was in the form of running 400m x 5 with a percentage of dehydration of 2%. Furthermore, the data were analyzed using SPSS 26.Results. The results showed a significance value of 0.241> 0.05, it can be concluded that there is no significant difference before and after dehydration on body balance. However, the calculation results can be seen that the mean balance will decrease if the body is dehydrated.Conclusions. Although there is a variation in the mean value, the difference does not reach the level of statistical significance. Thus, it can be concluded that body balance is not significantly affected by fluid loss before and after dehydration.